Journal of Pharmacy & Pharmacognosy Research: Welcome - Gabino Garrido (GarVal Editorial Ltda., 2013)
Open access is becoming increasingly evident, making the free access to texts a fact increasingly common. Also, the free availability of full scientific papers in electronic format on the Internet has proven to be the fastest and most effective way to disseminate or access to scientific information. Therefore, there is a boom in the creation of scientific journals available in online full text in most countries. However, in Chile there is little chance for pharmacists to publish their scientific work, given the lack of a journal to represent them. Arises is why the Journal of Pharmacy & Pharmacognosy Research, an international journal, in English and Spanish, specialized and peer review, open access, which publishes scientific studies in pharmacognostic and pharmaceutical fields. This journal will publish research articles, reviews, commentaries and letters to the editor, as well as special editions and reviews of book and undergraduate and graduate theses of pharmacists or professionals involved in Pharmaceutical Sciences or Pharmacognosy. The emergence of a scientific journal, plus an intellectual event, is a major financial and human challenge. We want to share this challenge with you, readers and future authors of the articles in this, your journal. Welcome!